Cultivating group cohesiveness: The role of collective energy - Muceldili, Busra; Erdil, Oya (Elsevier Science Bv, 2015)
Despite the growing research interest both positive psychology and positive organizational scholarship, the studies about collective energy at work remains nascent. In this study, we examine the role of collective energy (in the aspect of affective and behavioral) for enhancing group cohesiveness. Based on a sample of 127 service employees, our findings indicate connectivity is positively related to both affective energy and behavioral energy and both affective energy and behavioral energy is positively related to group cohesiveness. The study contributes the understanding the role of connectivity for enhancing energy in groups. The empirical findings of this study will lead to both scholars and practitioners to better understand collective energy within service industries. (C) 2015 The Authors. Published by Elsevier Ltd.
11th International Strategic Management Conference -- JUL 23-25, 2015 -- Vienna, AUSTRIA
Keywords: Energy; high quality connection; cohesiveness; connectivity; positive organizational scholarship